An Error Analysis on Verb Usage in texts written by EFL High School Students - Ulfa Vazariah; Yenni Rozimela (Journal of English Language Teaching, 2020)
This study aimed to analyze verb errors and types of errors made by senior high school students in writing a text. Source of data in this research is 27 pieces of students writing task written by EFL Senior High School (In this study; XII MIPA 7 SMAN 1 Padang in Academic Year 2019/ 2020). This research was descriptive research used in analysing verbs errors in the texts. The instruments used in this research was students’ writing task. The errors were classified into four categories based on Surface Strategy Taxonomy of Dulay’s Theory. Those were omission, addition, misformation, and misordering. Then, the percentage of verb errors was used to determine the verb errors and types of errors. The findings of the research showed that all of types of errors found in students’ writing. There were 164 verb errors foud. The most type of errors was misformation errors. It was followed by omission errors. The, the least errors were addition followed by misordering errors. Then, Another finding was main verb as the highest verb types which mostly errors in students’ writing.